THE EFFECT OF COUNSELING ON KNOWLEDGE AND ATTITUDES TOWARD MENARCHE IN CLASS VII STUDENTS OF MTSN 1 KUTA BAROE KEC. IDI TUNONG KAB. EAST ACEH IN 2019 - KAMELIA SINAGA (LP2MTBM MAKARIOZ, 2020)
Menarche occurs during adolescence and brings unbalanced changes between physical and mental health, making youngwomen sad, anxious and less eager to carry out tasks at school that cause unstable achievement of young women so that itcan be said that female students do not have the readiness to face menarche. Menarche counseling has never been done atthis school. To determine the Effect of Counseling About Menarche On Knowledge and Attitudes Toward Menarche. Type ofResearch Quasy Experiment with One Group Pre Test - Post Test Design. A sample of 40 students, taken by purposivesampling technique. Data collection tool is SAP about menarche and questionnaire. Data were tested with Wilcoxon test.The Effect of Counseling on Knowledge and Attitudes Toward Menarche in Class VII Students at MTsN 1 Kuta Baroe in2019, with a sample of 40 Class VII students, it was concluded that: From the statistical test results obtained p-value (0,000<0.05) . Then it can be concluded that there is an influence between Counseling on Knowledge and Attitudes TowardSignificant Menarche. There is an influence between Counseling on Knowledge and Attitudes Toward a SignificantMenarche in Class VII Students at MTsN 1 Kuta Baroe.